2019
DOI: 10.3390/ijms20184504
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistance in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC), generally known as pancreatic cancer (PC), ranks the fourth leading cause of cancer-related deaths in the western world. While the incidence of pancreatic cancer is displaying a rising tendency every year, the mortality rate has not decreased significantly because of late diagnosis, early metastasis, and limited reaction to chemotherapy or radiotherapy. Adjuvant chemotherapy after surgical resection is typically the preferred option to treat early pancreatic cancer. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
306
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(348 citation statements)
references
References 122 publications
4
306
0
1
Order By: Relevance
“…A common feature of human tumors is an ECM-rich microenvironment with high density of collagen and hyaluronan. This mass often surrounds nests of tumor cells and increases the distance from blood vessels to tumor cells, thus decreasing drug delivery of even small molecules [ 21 , 22 ]. The growth of tumor cells and matrix lead to solid stress and a consecutive compression of micro vessels, especially lymphatic vessels, leading to decreased convection and increased interstitial fluid pressure.…”
Section: Angiotensin Inhibition: How An Old Drug Shows New Tricksmentioning
confidence: 99%
“…A common feature of human tumors is an ECM-rich microenvironment with high density of collagen and hyaluronan. This mass often surrounds nests of tumor cells and increases the distance from blood vessels to tumor cells, thus decreasing drug delivery of even small molecules [ 21 , 22 ]. The growth of tumor cells and matrix lead to solid stress and a consecutive compression of micro vessels, especially lymphatic vessels, leading to decreased convection and increased interstitial fluid pressure.…”
Section: Angiotensin Inhibition: How An Old Drug Shows New Tricksmentioning
confidence: 99%
“…However, the development of chemoresistance among PDAC patients leads to poor clinical outcomes. Studies focused on this disease suggested that PDAC chemoresistance is a result of the interaction between pancreatic cancer cells, cancer stem cells, and the tumor microenvironment [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of chemoresistance among PDAC patients leads to poor clinical outcomes. Studies focused on this disease suggested that PDAC chemoresistance is a result of the interaction between pancreatic cancer cells, cancer stem cells, and the tumor microenvironment [4][5][6][7][8][9]. Several risk factors have been associated with PDAC, including tobacco smoking, diabetes mellitus, obesity, dietary factors, alcohol abuse, age, ethnicity, family history and genetic factors, Helicobacter pylori infection, belonging to non-0 blood group, and chronic pancreatitis [6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various microenvironmental factors are the stromal fibroblasts that secrete the pro-inflammatory cytokines, which in turn activate oncogenic transcription factors within the tumor epithelial cells. These transcription factors (STAT3, NF-kB) often trigger a cascade of events that trigger self-renewal pathways regulated by Sox2, Oct4 and Nanog1, thereby promoting a stemness-associated phenotype [ 7 , 8 ]. Our research in pancreatic cancer (currently under revision) shows that stromal cells secrete IL6 which activates the STAT3 signaling pathway within the tumor cells which invariably leads to the enrichment for stemness.…”
Section: Extracellular Matrix As a Niche For Cancer Stem Cell Formmentioning
confidence: 99%